Answer:
x = -2
Explanation:
![3x^2+12x+12=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/l8rvsv9h0uiyf75uedveb2wxedr1vvcu7g.png)
First, try to factor out a common factor from every term.
The coefficients are 3, 12, and 12.
The GCF (greatest common factor) of 3, 12, and 12 is 3, so factor out a 3 from all terms.
![3(x^2+4x+4)=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/tjthigeso4ky23isogiu1u4bi4pid21zz8.png)
Now divide both sides by 3.
![x^2+4x+4=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9522vxsb3ngecqdyhenamvsu2jy83bw89f.png)
You have a quadratic trinomial of the form x^2 + ax + b.
To factor it, you need to find two numbers that multiply to b and add to a. Call these two numbers p and q.
Then the factorization is (x + p)(x + q).
In your case, you have
![x^2 + 4x + 4 = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/f8lg2nhtg4lgky1i99eqlrsfsg9xnwpwfj.png)
In this case, a = 4 and b = 4.
You need two numbers that multiply to 4 and add to 4.
The numbers are 2 and 2.
Then the factorization is
Now set each factor equal to zero and solve for x.
x + 2 = 0 or x + 2 = 0
x = -2 or x = -2
Answer: x = -2